Development and Research of Concentrator-Sonotrode with Increased Radiating Surface - KHMELEV, Sergei; KHMELEV, Vladimir; GOLYKH, Roman; SHALUNOV, Andrey (Archives of Acoustics, 2015)
This paper presents the results of studies on functional possibilities of the optimization of geometric sizes and the design development of specialized resonance concentrating link (concentrator-sonotrode) with enlarged radiating surface. Developed theoretical model allows to determine the value of longitudinal and transverse sizes of each part of concentrating link providing the achievement of required features of the ultrasonic vibrating systems (gain factor of the unit and its resonance frequency). To verify the efficiency of designed model, the geometric sizes of resonance concentrating link were determined using the finite-element complex, which showed that the disagreement did not exceed 10%. The efficiency of proposed model at the determining of size and resonance characteristics of concentrating link was proved by the experiments.Theoretical and experimental studies helped to optimize the size of concentrating link while the vibrating system developed on its base enabled the enlargement of radiating surface without decreasing the radiation intensity for the realization of technologies of cavitation treatment of liquid media.